The one-humped wonder: Ethiopia’s camels in focus - Megersa, B.; Amenu, Kebede; Knight-Jones, Theodore J.D.; Jemberu, Wudu T. (Livestock Data For Decisions, 2024)
As the United Nations marks 2024 as the International Year of Camelids, we explore some key facts about Ethiopia’s camels, and their crucial but underappreciated role in supporting livelihoods and food security in the face of climate change.